Fine tuning of social integration by two myrmecophiles of the ponerine army ant, leptogenys distinguenda - Hashim, Rosli; Schulz, S.; Witte, V.; Foitzik, S.; Maschwitz, U. (Springer Verlag, 2009)
Myrmecophiles are animals that live in close association with ants and that frequently develop elaborate mechanisms to infiltrate their well-defended host societies. We compare the social integration strategies of two myrmecophilic species, the spider, Gamasomorpha maschwitzi, and the newly described silverfish, Malayatelura ponerophila gen. n. sp. n., into colonies of the ponerine army ant, Leptogenys distinguenda (Emery) (Hymenoptera: Formicidae). Both symbionts use chemical mimicry through adoption of host cuticular hydrocarbons. Exchange experiments between L. distinguenda and an undetermined Leptogenys species demonstrate that reduced aggression toward alien ants and increased social acceptance occurred with individuals of higher chemical similarity in their cuticular hydrocarbon profiles. We found striking differences in chemical and behavioral strategies between the two myrmecophiles. Spider cuticular hydrocarbon profiles were chemically less similar to the host than silverfish profiles were. Nevertheless, spiders received significantly fewer attacks from host ants and survived longer in laboratory colonies, whereas silverfish were treated with high aggression and were killed more frequently. When discovered and confronted by the host, silverfish tended to escape and were chased aggressively, whereas spiders remained in contact with the confronting host ant until aggression ceased. Thus, spiders relied less on chemical mimicry but were nevertheless accepted more frequently by the host on the basis of behavioral mechanisms. These findings give insights into the fine tuning of social integration mechanisms and show the significance of qualitative differences among strategies.